2016
DOI: 10.1016/j.aca.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of bacterial endotoxins in ophthalmic viscosurgical device materials by direct analysis in real time mass spectrometry

Abstract: Bacterial endotoxins are lipopolysaccharides bound to the bacterial cell wall and released when bacteria rupture or disintegrate. Possible contamination of endotoxin in ophthalmic devices can cause a painful eye inflammation or result in toxic anterior segment syndrome after cataract surgery. Measurement of bacterial endotoxin in medical device materials is difficult since endotoxin binds with polymer matrix and some of the materials are very viscous and non-water soluble, where traditional enzyme-based Limulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…There are a lot of methods to measure biomolecules, such as sensitive detection of deoxyribonucleic acid [ 10 ], grow factors [ 11 ], and cells [ 12 ]. Many of them have been used to detect them for a long time to the present, such as those based on fluorometry, spectrophotometry, or chemiluminescence [ 13 ], localized surface plasmon resonance (LSPR) [ 14 ], mass spectrometry [ 15 ], optical methods [ 16 ], the electronic tongue [ 17 ], the voltammetric method [ 18 ], and electrochemistry [ 19 ]. Almost all of them have showed great disadvantages such as: high costs, long operating times, and use of labeled molecules.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of methods to measure biomolecules, such as sensitive detection of deoxyribonucleic acid [ 10 ], grow factors [ 11 ], and cells [ 12 ]. Many of them have been used to detect them for a long time to the present, such as those based on fluorometry, spectrophotometry, or chemiluminescence [ 13 ], localized surface plasmon resonance (LSPR) [ 14 ], mass spectrometry [ 15 ], optical methods [ 16 ], the electronic tongue [ 17 ], the voltammetric method [ 18 ], and electrochemistry [ 19 ]. Almost all of them have showed great disadvantages such as: high costs, long operating times, and use of labeled molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Endotoxins are responsible for the toxic effects that cause fevers, 1 septic shock, 2 and sepsis. 3,4 Biosensor based endotoxin detection has been widely investigated recently, 5,6 and many methods have been investigated to identify endotoxins: hydrophobic interactions, 7 localized surface plasmon resonance (LSPR), 8 mass spectrometry, 9 optical methods, 10 the electronic tongue, 11 the voltammetric method, 12 and electrochemistry. [13][14][15][16][17] However, these methods have some disadvantages, such as high costs, a long processing time and the requirement of labeled markers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a couple of studies have shown that large glycosaminoglycan and lipopolysaccharide can break down into small fragments instantaneously in DART source. 40,41 Nemes et al reported that heparin and its infamous adulterant, oversulfated chondroitin sulfate, can be differentiated through the characteristic small products (m/z < 300) obtained with DART-MS. 40 It is also shown in the literature that large endotoxin molecules can be broken into small fragments (m/z < 450) in the DART source in seconds, and the fragments provide the basis for rapid detection of bacterial endotoxin contamination in medical materials. 41 In the present study, six traditional Chinese herbal medicines, Dendrobium of f icinale (DO), D. nobile (DN), Codonopsis pilosula (CP), Astragalus membranaceus (AM), Poria cocos (PC), and Lentinus edodes (LE) were used to test the potential of using DART-MS-based method for the molecular level characterization of polysaccharides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…40,41 Nemes et al reported that heparin and its infamous adulterant, oversulfated chondroitin sulfate, can be differentiated through the characteristic small products (m/z < 300) obtained with DART-MS. 40 It is also shown in the literature that large endotoxin molecules can be broken into small fragments (m/z < 450) in the DART source in seconds, and the fragments provide the basis for rapid detection of bacterial endotoxin contamination in medical materials. 41 In the present study, six traditional Chinese herbal medicines, Dendrobium of f icinale (DO), D. nobile (DN), Codonopsis pilosula (CP), Astragalus membranaceus (AM), Poria cocos (PC), and Lentinus edodes (LE) were used to test the potential of using DART-MS-based method for the molecular level characterization of polysaccharides. As a result, DART coupled to high resolution MS produced characteristic fragment ions (m/z < 350) for different types of plant polysaccharides within seconds, providing limit of detection (LOD) ranging from 0.01 to 0.1 ng mL −1 in aqueous solution.…”
Section: ■ Introductionmentioning
confidence: 99%